THE IMPLEMENTATION OF DEBATE TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN SPEAKING - Farisha Andi Baso (Universitas Muhammadiyah Makassar, 2016)
This study aimed at finding out the students’ speaking skill by using debate.The research design used a pre-experimental, in which it used the pre-test and post-test comparison to find out the result of the research. The population of the research was all students of the Eleventh Grade Students of SMA Perguruan Tinggi Islam Makassar which consisted of three classes. Each class consists of more than 20 students, so the total number of population was 85 students. Among the total number of population, the researcher took one class to be a sample of this research by using purposive sampling technique. The instruments of this research were speaking test and recording. To analyze the score of the students’ achievement in pre-test and post-test, the researcher used t-test analyses. The result of the data showed that there was a significant difference between pre-test and post-test. The value of t-test (6.35) was greater than the t-table (1.729) at the level of significant (p) = 0.05 and degree of freedom (df) = 19. It can be said that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Which means that there was a significant difference between the students’ speaking ability before and after using debate or it can be said that the use of debate was effective in improving the students’ speaking skill at the Eleventh Grade of SMA Perguruan Tinggi Islam Makassar?Keywords: Debate Technique, Speaking Ability